Teknologi Artificial Intellegence dan Nilai-Nilai Karakter Mahasiswa Universitas Islam Negeri Datokarama Palu: Artificial Intelligence Technology and the Character Values of Students at Datokarama State Islamic University, Palu - Elfira, Riska (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2024)
The aim of the research is to analyze the use of artificial intelligence (AI) technology and its impact on the character values ​​of students at Datokarama State Islamic University, Palu. In this technological era, AI is used in various fields, including education, which can influence the way students learn and interact. The research used a qualitative method approach, data collection was carried out through surveys and interviews with students and lecturers. The research results show that the application of AI in the teaching and learning process not only increases academic efficiency, but also contributes to the formation of student character, such as collaboration, Critical Thinking, creativity and self-confidence. Lecturers' efforts to strengthen character values ​​by providing examples, integrating values ​​in learning, creating a conducive learning environment, individual guidance and conducting comprehensive evaluations. This research recommends the wise use of AI in learning activities. The use of AI must be in line with strengthening character values ​​in students. It is hoped that these findings can become a reference for educational institutions in utilizing AI technology wisely to improve the quality of learning and student character.